Crosswinds : the Air Force's setup in Vietnam - Tilford, Earl H. (College Station : Texas A & M University Press, 1993)
Who lost the war in Vietnam? Popular mythology has blamed politicians, the press, or Jane Fonda and the antiwar movement. Crosswinds, a riveting and incisive analysis by a former Air Force officer who served as an intelligence specialist during the war, demonstrates convincingly that the U.S. Air Force was indeed "set up" for defeat, but not by an America that tied its hands. Rather, the Air Force was a victim of its own history, its institutional values, and an intellectually ossified leadership which could not devise a strategy appropriate to the war at hand. These factors within the Air Force itself created heavy flying.
To many airmen and military analysts, the color of the flag over Ho Chi Minh City was the result of political betrayal of an Air Force that had delivered an unbroken string of unmitigated tactical victories. Many embrace the myth that the Christmas Bombing of December, 1972, for instance, had brought Hanoi to its knees before the politicians called the military off. Moreover, these commentators argue that the same "victory" could have been had at any time during the war if only air power had been unleashed. Yet, Earl Tilford convincingly demonstrates that - in spite of the nearly eight million tons of bombs dropped in Indochina, the 2,257 Air Force planes lost, and the untold thousands of people killed - air power failed to achieve victory
This book examines the entire Air Force experience in Southeast Asia, including the "secret wars" in Laos and Vietnam. Using previously untapped, recently declassified sources, Tilford challenges the accepted Air Force interpretation that it was betrayed. Tackling the issues of the air war, he traces the doctrine of strategic bombing from its roots in World War II through its development in the 1950s and early 1960s as a response to the Soviet threat abroad and interservice rivalries at home. In concluding, he compares the debacle of the Vietnam air war with the strategies of the subsequent Gulf war. Crosswinds is a powerful piece of writing, thoroughly researched and convincingly argued. It will contribute mightily to the ongoing attempt to understand what happened in Southeast Asia and why.
Includes bibliographical references (pages 230-239) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: United States. -- Air Force -- History -- Vietnam War, 1961-1975.; United States. -- Air Force; Vietnam War, 1961-1975 -- Aerial operations, American; Guerre du Viêt-nam, 1961-1975 -- Opérations aériennes américaines.; HISTORY -- Military -- Vietnam War; Military operations, Aerial -- American; 1961-1975; History